Pengaruh Kemampuan Penalaran dan Representasi Matematis terhadap Hasil Belajar Matematika Kelas VIII di SMP - Afriliani Rismayanti; Sudi Prayitno; Muhammad Turmuzi; Hapipi Hapipi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This Research aims to know about the reasoning ability and mathematic representation ability to the results of mathematic lesson in students grade VIII SMP Negeri 1 Batulayar year academic 2019/2020. This research used quantitative approach with ex post facto research type. The population of this research is the eighth grade students of SMP Negeri 1 Batulayar. In determining the sample, probability sampling technique with the type of cluster sampling was used. The sample in this research is the students of class VIII B SMP Negeri 1 Batulayar amounted to 22 students. Data analysis used was multiple linear regression analysis. From the result of the data analysis we found the significant influence between reasoning ability and representative mathematic’s ability to the mathematics learning result of mathematic lesson in students grade viii smp negeri 1 batulayar year academic 2019/2020 with Fcount = 78,812 > F(2,19) = 3,52. The data we wroute as the same regration that Ŷ=-2,452+0,466X1+0,575X2. The equation show us that reasoning ability and the representative mathematic’s ability increase 1 unit and the learning result will increase to 0,466 from reasoning mathematics ability plus 0,575 representative mathematic’s ability.